Analysis of Motivation and Interests of Arabic Language Education Students at Unismuh Makassar in Educational Statistics Subject - Susilawati, Sumarni (Yayasan Insan Literasi Cendekia (INLIC) Indonesia, 2023)
Education statistics subject is one of the compulsory subjects for students majoring in education which is often avoided by many students. Students tend to have a negative attitude towards subjects related to numbers and calculations. Based on the observation results of Arabic Language Education student exam results, there are still many students who have not been able to describe or analyze the results of data processing. Thus, research was conducted regarding the interest and motivation of Arabic Language Education students in the Education Statistics subject. The research method used is the questionnaire method to measure aspects of interest and talent, aspects of learning readiness, and learning support facilities. So the results obtained from the study were that 85.7% of students liked the Education Statistics subject, and prepared the media to record material well. The presence of lecturers in the room also affects student enthusiasm for learning. It's just that the enthusiasm for student learning has not been supported by adequate facilities.